Organisms Composing an Experimental Coral Reef Community from Mo'orea, French Polynesia, Exhibit Taxon-Specific Net Production: Net Calcification Ratios - Lantz, Coulson A.; Carpenter, Robert C.; Comeau, Steeve; Edmunds, Peter J. (Frontiers in Marine Science, 2017)
Current research on coral reefs seeks to link the responses to anthropogenic stressors (such as global warming and ocean acidification [OA]) among differing functional levels of biological organization. While experimental studies have identified ex situ taxon-specific responses to OA and global warming, isolating and connecting these effects in situ at the community-level has proved difficult. The difficulties arise from the large number of naturally varying parameters affecting corals reefs, such as light intensity and seawater residence time that affect net community production and calcification. To control variation in seawater residence time and allow light intensity to vary naturally, experimental outer reef (17-m depth) benthic communities composed of calcified algae, corals, and reef pavement were constructed in large outdoor flumes in Mo’orea, French Polynesia. Net community production (P), net community calcification (G), the ratio of P/G (P/Gratio), and slope of P regressed on G (P/Gslope) were calculated for the communities, and concurrently for the constituent members under the same temperature, light, and flow conditions. P and G, for both the communities and constituent members, were correlated positively with light intensity, whereas P/Gratio and P/Gslope were unaffected by light intensity. P/Gratios and P/Gslopes exhibited values that were specific to each community member. These results suggest that the P/Gratio and P/Gslope may be unaffected by natural variability in light intensity and could serve as useful metrics to relate responses at the taxon and community level, which is an important step in assessing the effects of environmental changes on coral reefs.